“I felt shamed and blamed”: an exploration of the parental lived experience of school distress - Mullally, Sinéad L.; Connolly, Sophie E. (Frontiers in Psychiatry, 2025)
IntroductionSchool Distress refers to a child or young person’s (CYP) difficulty attending school due to the extreme emotional distress associated with school attendance. Limited research exists on the impact of School Distress on the parents/carers supporting these CYP.MethodsUsing a case–control, concurrent embedded mixed-method design, we explored this lived experience. 947 parents of CYP with School Distress completed a bespoke on line questionnaire, alongside two control parent groups (n=149, n=25) and one professional group (n=19).ResultsFindings revealed a devastating impact on the mental health of parents, with parents displaying significantly heightened daily anxiety and significantly lower mood during, but not before, their children’s school attendance difficulties. In addition, parents with children experiencing School Distress reported significantly higher negative emotion states and significantly lower positive emotion states. Parents also reported overwhelmingly negative treatment from professionals, including being disbelieved or blamed for their child’s difficulties, threatened with fines and court action, and disempowered by the actions of professionals surrounding their child. Significant, deleterious impacts were also evident across all aspects of their lives, including their careers, finances, and other children. Perhaps unsurprisingly, half of these parents reported developing a new mental health condition since their child’s difficulties began, with the experience itself rated as the second most threatening potential life event, superseded only by the death of a first-degree relative (including a child or spouse). On the other hand, professionals working with CYP with School Distress did not experience these deleterious mental health or wider life consequences. Despite understanding how threatening the experience is for parents, they were often quick to blame parents for their children’s difficulties. Professionals, like parents, expressed frustration with the lack of help available for these CYP and their families.DiscussionThis study highlights a bleak, adversarial, and lonely picture for parents of CYP struggling to attend school. More specifically, the findings depict a system rife with parental blame; a system that appears to isolate parents through hostile, threatening, and punitive actions. A wider lack of societal understanding of the experience of School Distress further compounds this dearth of support for parents, placing parental mental health in further peril.